中国会诊联络精神医学现状(英文) - 季建林 叶尘宇 (上海精神医学, 2012)
Consultation-liaison psychiatry (CLP) was first established in China after liberation in 1949. It has developed more rapidly over the last two decades but, despite major regional differences in the level of CLP, the overall practice of CLP in the country remains quite basic, largely limited to case-based consultation with other medical departments. There is little ongoing collaboration between departments of psychiatry and other departments, and medical students and non- psychiatric clinicians rarely get training in CLP.